1988
DOI: 10.1148/radiology.167.3.3363123
|View full text |Cite
|
Sign up to set email alerts
|

Does preoperative needle localization lead to an increase in local breast cancer recurrence?

Abstract: Between 1978 and 1981, 74 women with nonpalpable breast cancer underwent surgery after localization guides were placed. In 72 patients, guides were introduced parallel to the chest wall; in two the needle was positioned anteroposteriorly under computed tomographic guidance. Fifty-six cases (76%) were infiltrating cancer; 13 (17%), intraductal cancers; two (3%), inflammatory; and three (4%), lobular carcinoma in situ. Surgery was not used to treat the latter five patients. In the remaining 69 women, 42 (61%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…In any case, the clinical significance of needle tract seeding remains uncertain (11,(20)(21)(22). On the one hand, the excision of the entire needle tract at the time of definitive surgery has been recommended to avoid local recurrence (12,18,(23)(24)(25)(26); on the other, authors believe that excision of the entire needle tract is neither feasible nor advisable as a routine measure since radiotherapy is advised for both DCIS and IDC after breast-conserving surgery (16). It is worth mentioning that a recent large series showed that preoperative core needle biopsy was not associated with increased local recurrence rate in the context of breast-conserving surgery and postoperative radiotherapy (27).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the clinical significance of needle tract seeding remains uncertain (11,(20)(21)(22). On the one hand, the excision of the entire needle tract at the time of definitive surgery has been recommended to avoid local recurrence (12,18,(23)(24)(25)(26); on the other, authors believe that excision of the entire needle tract is neither feasible nor advisable as a routine measure since radiotherapy is advised for both DCIS and IDC after breast-conserving surgery (16). It is worth mentioning that a recent large series showed that preoperative core needle biopsy was not associated with increased local recurrence rate in the context of breast-conserving surgery and postoperative radiotherapy (27).…”
Section: Discussionmentioning
confidence: 99%
“…Kopans et al found no local recurrences in 74 patients who had undergone needle localization prior to excisional biopsy and were followed for up to 78 months. 2 However, only 21 of these women were treated with breast conservation. The majority were treated by mastectomy, removing the entire needle track.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of stagematched palpable invasive breast cancer treated by mastectomy, Berg and Robbins [89] noted no difference in 15-year survival between women whose cancer is diagnosed on aspiration biopsy and those whose cancer is diagnosed with open surgical biopsy. In a study of 74 women with nonpalpable breast cancer diagnosed by needle localization and surgical biopsy, Kopans et al [90] reported no evidence of local recurrence attributable to needle localization. Mastectomy was performed in all the patients in the study of Berg and Robbins and most of the patients in the study of Kopans et al, limiting the conclusions that can be drawn about needle track recurrence.…”
Section: Epithelial Displacementmentioning
confidence: 99%